A posteriori comparisons, repeated instances and urban policy mobilities: What 'best practices' leave behind. (June 2022) - Montero, Sergio; Baiocchi, Gianpaolo
Urban studies scholars have engaged in a lively debate on how to reformat comparative methods in the face of critical scrutiny of the discipline's purported universalism. We share the enthusiasm for a reformatted urban comparativism and, in this paper, we turn to the thorny and more pragmatic question of how to actually carry it out. While traditional comparisons in urban studies have sought to find variation among similar cases by selecting a priori, in this article we propose to compare the findings of different researchers through a posteriori, that is, after the research has been done. We also argue that urban researchers need to focus on urban processes rather than cities; on repeated instances rather than on controlling for difference; and on mid-level abstraction rather than on grand theory or descriptive empirical cases. We put this strategy to work by comparing empirical research previously carried out by the authors on how two Latin American cities became international urban 'best practices': Bogotá as a sustainable transport model and Porto Alegre as a model of local participatory budgeting. The comparison highlights the tension between the simplified policy narratives that were mobilised to circulate Bogotá and Porto Alegre as international 'best practices' and the broader multi-scalar institutional reforms that these 'best practice' narratives have left behind in their global circulations. In doing so, we show the potential of a posteriori comparisons to analyse contemporary global urban dynamics and provide some explicit methodological tactics on how to do comparisons in a more systematic way.